Quality incentive contracts considering asymmetric product manufacturability information: Piece rate vs. Tournament. (June 2020) - Gao, Jie; Fan, Huirong; Cao, Bin; Wang, Nengmin
Highlights: The asymmetric product manufacturability information is considered. Both piece rate and tournament contracts are analyzed in the signaling models. The existence and stability of separating equilibriums are analyzed. Abstract: Product quality depends on not only the quality effort spent during the manufacturing process but also the product manufacturability determined at the product design stage. The manufacturer (he) may keep the product design and a part of production in house and outsource some production when he encounters a large unexpected demand. In this case, he may privately own the product manufacturability information (low- or high-type) and should propose an incentive-compatible contract to signal this information to the uninformed supplier. We first consider that the manufacturer outsources to one supplier and proposes a piece rate contract, with which the supplier is charged a quality penalty proportional to the amount of defective products supplied. In the separating equilibrium, the high-type manufacturer employs a smaller quality penalty rate and thus achieves a lower product quality under asymmetric product manufacturability information than under symmetric information. When the manufacturer outsources to multiple suppliers, he can employ a tournament contract, with which the quality penalty is based on the suppliers' relative performance. In this situation, the equilibrium tournament contract under symmetric product manufacturability information is also the separating equilibrium contract under asymmetric information, hence resulting in the first-best quality and profit. We further find that the separating equilibrium exists and is stable while no pooling equilibrium is stable.